Analisis Standar Keamanan dan Pelayanan Terhadap Keselamatan Penerbangan di Bandar Udara I Gusti Ngurah Rai Bali - Apriliyana Asri; Muhammad Sabilal Alief; Lilis Kurnianingsih (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Aviation safety is a crucial component in the aviation industry, and the implementation of consistent service and security standards across all airport environments is an essential part of flight safety. All these aspects have been regulated by ICAO, which is responsible for regulating and establishing flight standards worldwide. This research investigates how security and service standards are applied at I Gusti Ngurah Rai International Airport in Bali and how this impacts the operational safety of flights. This study was conducted using a literature review method, sourced from 8 news articles, 9 journals  and conducted interviews through electronic media to verify the conditions on the ground. The quality of terminal operations supervision services and passenger services at the terminal is the main topic of the research. The results of this study show that the majority of safety procedures have been implemented in accordance with regulations. The application of good service and security standards greatly helps to maintain flight safety and increase the confidence of airport service users.